(untitled) (Journal of EAHIL, 2016)
This study aimed to record the experiences of health information professionals practising across Europe, to provide data to aid career planning, support strategic decision-making for information services, and understand the impact health professionals have. Interviews, surveys, and focus groups were used to gather data to understand the roles of information professionals, and how they support healthcare. Roles have developed, encompassing healthcare challenges, often embracing technologies and pushing the boundaries of traditional library roles. Respondents demonstrated the impact mainly through their evidence based skills. This study enhances our understanding of the complexity of the domain, how it is evolving and impacting on healthcare.